8-Hydroxydeoxyguanosine Urine and Total Nitric Oxide Serum in Chronic Kidney Disease - Ahadini, Putri Aliya; Thaha, Mochammad; Mustika, Arifa (Folia Medica Indonesiana, 2022)
Highlights: • Oxidative markers 8-Hydroxydeoxyguanosine and Nitric Oxide was found high in hemodialysis and non-hemodialysis chronic kidney disease patients. • There is no correlation between 8-Hydroxydeoxyguanosine and Nitric Oxide in hemodialysis and non-hemodialysis chronic kidney disease patients. Abstract: Oxidative stress is essential to chronic kidney disease (CKD). Several markers include 8-Hydroxydeoxyguanosine (8-OHdG) and Nitric Oxide (NO). Reactive oxygen species (ROS) and Reactive Nitrogen Species (RNS) increased in CKD and had a role in renal impairment progressivity. There are some controversies regarding oxidative markers in CKD patients in several studies. This study aimed to understand oxidative markers 8-OHdG and NO and explained the correlation of both markers in hemodialysis and non-hemodialysis CKD patients. Twenty hemodialysis patients and forty-nine non-hemodialysis patients were enrolled in this cross-sectional study. Urine patients were collected to measure 8-OHdG using the enzyme-linked immunoassay (ELISA) method, and NO was measured from serum patients using the Griss Saltzman method. Based on Bivariate Pearson analysis, there was no significant correlation between 8-OHdG urine and total NO serum in the hemodialysis group (p= 0,510, p>0.05) and in the non-hemodialysis group (p= 0.801, p>0,05). In this study, DNA oxidative marker, 8-OHdG, was not correlated with NO in CKD patients.